Pengaruh Iklim Organisasi dan Kompensasi Terhadap Motivasi Kerja dan Kepuasan Kerja pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Tapanuli Tengah - Mariati Simanullang (Jurnal Riset Manajemen dan Bisnis, 2021)
This study aims to analyze the direct and indirect effects of organizational climate, and compensation for work motivation of employees in the Community and Village Empowerment Service of Tapanuli Tengah Regency. The method used is the quantitative method of causality. The population in the study was 37 respondents. The results showed that organizational climate, compensation had a direct effect on employee motivation in the Community and Village Empowerment Service of Tapanuli Tengah Regency and had a positive and significant effect on employee job satisfaction. Then the organizational climate and compensation indirectly have a positive but insignificant effect on job satisfaction through the work motivation of the employees of the Community and Village Empowerment Service of Tapanuli Tengah Regency.